Section 42 ET Amendment - Nores Torres, Luis Enrique (LABOS Revista de Derecho del Trabajo y Protección Social, 2022)
Real Decreto Ley 32/2021, December 28 th, has modiﬁed diﬀerent parts of the Estatuto de los Trabajadores, among them, section 42. That section sets up over the employer who outsource his production a joint and several liability on certain obligations contracted by the contractor and the subcontractor with their workers, but just in case that these obligations were born within the term of the outsourcing. The purpose of this paper is to outline the contour and content of the legislative reform on section 42 ET.